Industrial engineering non-traditional applications in international settings - Bidanda, Bopaya; Sabuncuolu, Ihsan; Kara, Bahar Y (Engineering - Industrial & Manufacturing, 2014)
Industrial Engineering Non-Traditional Applications in International Settings raises the bar and examines industrial engineering from a global perspective. Representing the best papers from the International Institute of Industrial Engineers (IIIE) conference held in Istanbul in June 2013, and developed by contributors from at least six different countries, this material lends their expertise on the international impact of industrial engineering applications and provides a thorough understanding of the subject